The MRI diagnosis and management of incomplete intertrochanteric fractures of the femur. - Alam, A; Willett, K; Ostlere, S (2005)
Incomplete intertrochanteric fractures do not extend across to the medial femoral cortex and are stable, without rotational deformity or shortening of the lower limb. The aim of our study was to establish whether they can be successfully managed conservatively. A total of 68 patients over a five-year period presented with a suspected fracture of the femoral neck and underwent an MRI scan for further assessment. From these, we retrospectively reviewed eight patients with normal plain radiographs but with an incomplete, intertrochanteric fracture on MRI scan. Five were managed conservatively and three operatively. The mean length of hospital stay was 16 days for the conservatively-treated group and 15 days for those who underwent surgery; this was not statistically significant (p > 0.5) and all patients were mobilised on discharge. Although five patients were readmitted at a mean of 3.2 years after discharge, none had progressed to a complete fracture. We believe that patients with incomplete intertrochanteric fractures should be considered for conservative treatment.